2014
DOI: 10.1016/j.renene.2013.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Data efficient measure-correlate-predict approaches to wind resource assessment for small-scale wind energy

Abstract: Paper:Weekes, SM and Tomlin, AS (2014) Highlights: Long-term wind energy resource predicted using just three months onsite wind speed measurements.  Robust error statistics obtained using 120 test periods at 22 sites over 11 years.  Link between measurement season and prediction accuracy investigated.  Data-driven prediction approaches compared to semi-empirical boundary layer model. AbstractThe feasibility of predicting the long-term wind resource at 22 UK sites using a measurecorrelate-predict (MCP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…The subscripts and refer to the reference and target sites respectively. The baseline MCP approaches described above were applied previously to the meteorological monitoring sites used in this study for a fixed short-term measurement period of three months [9]. They are included here to serve as a comparison for assessing the success of the BW approaches using multiple measurement periods.…”
Section: Variance Ratio Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The subscripts and refer to the reference and target sites respectively. The baseline MCP approaches described above were applied previously to the meteorological monitoring sites used in this study for a fixed short-term measurement period of three months [9]. They are included here to serve as a comparison for assessing the success of the BW approaches using multiple measurement periods.…”
Section: Variance Ratio Methodsmentioning
confidence: 99%
“…Previous work [9] demonstrated that the success of the LR technique can be significantly improved by accounting for the residual errors. Hence, here is modelled using random samples from a zero-mean Gaussian distribution of the form:…”
Section: Linear Regressionmentioning
confidence: 99%
See 3 more Smart Citations